Elevational Gradients Impose Dispersal Limitation on Streptomyces - Hariharan, Janani; Buckley, Daniel H. (Frontiers in Microbiology, 2022)
Dispersal governs microbial biogeography, but the rates and mechanisms of dispersal remain poorly characterized for most microbial taxa. Dispersal limitation is driven by limits on dissemination and establishment, respectively. Elevation gradients create striking patterns of biogeography because they produce steep environmental gradients at small spatial scales, and these gradients offer a powerful tool to examine mechanisms of dispersal limitation. We focus on Streptomyces, a bacterial genus common to soil, by using a taxon-specific phylogenetic marker, the RNA polymerase-encoding rpoB gene. By targeting Streptomyces, we assess dispersal limitation at finer phylogenetic resolution than is possible using whole community analyses. We characterized Streptomyces diversity at local spatial scales (100 m to 3000 m) in two temperate forest sites located in the Adirondacks region of New York State: Woods Lake (< 100 m elevation change), and Whiteface Mountain (> 1000 m elevation change). Beta diversity varied significantly at both locations, indicative of dispersal limitation acting at local spatial scales, but beta diversity was considerably higher at Whiteface Mountain. Beta diversity varied across elevation at Whiteface Mountain, being lowest at the mountain’s base. We show that Streptomyces taxa exhibit elevational preferences, and these preferences are phylogenetically conserved. These results indicate that habitat preferences influence Streptomyces biogeography and suggest that barriers to establishment structure Streptomyces communities at higher elevations. These data illustrate that Streptomyces biogeography is governed by dispersal limitation resulting from a complex mixture of stochastic and deterministic processes.